Numerical modeling of the effect of temperature on the stability of mechanical equilibrium in binary gas mixtures - Mukamedenkyzy, V.; Akberdiyev, B. (Recent Contributions to Physics, 2026)
This work is devoted to studying the influence of temperature on the stability of mechanical equilibrium and the nature of mass transfer in binary gas mixtures in a gravitational field using the Ar–N₂ system as an example. It considers isothermal mixing of gases in a two-flask apparatus, in which the loss of mechanical equilibrium is caused by the formation of unstable concentration stratification of density during the mutual diffusion of components with different molecular weights. The main objective of the study is to establish the role of temperature in the formation and evolution of diffusion-convective mass transfer regimes at different pressures. To this end, numerical modeling was performed in the ANSYS Fluent software package in a three-dimensional setting using component transport equations and the SST k–ω turbulent model. Temperature is considered as an external parameter affecting the stability of the system through changes in the mutual diffusion coefficients and transport properties of the mixture. It has been established that temperature is a determining factor in the stability of mechanical equilibrium in a binary gas mixture. An increase in temperature leads to a weakening of concentration-driven gravitational convection due to an increase in the diffusion mobility of the components, which manifests itself both in the stabilization of the system near the stability boundary and in a decrease in the relative efficiency of convective transport in the region of developed convection. Numerical modeling made it possible to reconstruct the temporal dynamics of the mixing process and reveal the evolution of convective structures that is inaccessible to experimental measurements. The results obtained are in good agreement with experimental data and expand our understanding of the temperature control of diffusion-convective processes in binary gas systems.